Appendice. Schede e materiali dalla “Carta Archeologica della Civita di Tarquinia” (2018) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2019)
The aim of the article is to contextualize the contributions of this volume, which deals with different aspects related to the fortified perimeter and the archaeological finds from the neighbouring structures. Therefore, a selection of sheets of the "Archaeological Map of the Civita di Tarquinia" is presented. This work, carried out by the University of Milan and presented in the 2018 version, originates from the systematic research on structures and finds in the area of the ancient settlement from the centuries of the first discoveries to the present time.
Keywords: Tarquinia; fortifications; settlement; archaeological map; previous archaeological research